2007
DOI: 10.1103/physrevb.75.224413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and specific heat ofTbFe3(BO3)4: Experiment and crystal-field calculations

Abstract: We have studied the thermodynamic properties of single-crystalline TbFe3(BO3)4. Magnetization measurements have been carried out as a function of magnetic field (up to 50 T) and temperature up to 350 K with the magnetic field both parallel and perpendicular to the trigonal c-axis of the crystal. The specific heat has been measured in the temperature range 2-300 K with a magnetic field up to 9 T applied parallel to the c-axis. The data indicate a structural phase transition at 192 K and antiferromagnetic spin o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
82
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 21 publications
6
82
1
8
Order By: Relevance
“…"Heavier" rare-earth ions from Eu to Yb, and also Y cause a symmetry reduction to space group P3 1 21 upon lowering temperature which is manifested as a sharp peak at the transition temperature in specific-heat measurements. 1,3,13 The transition temperature T S depends basically on the size of the R-type ion present in the structure 6 and one observes a decreasing T S by increasing the R radius. In particular, one finds T S = 201.5 K, 155 K, and 445 K for the Tb-, Gd-, and Y-based compounds, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…"Heavier" rare-earth ions from Eu to Yb, and also Y cause a symmetry reduction to space group P3 1 21 upon lowering temperature which is manifested as a sharp peak at the transition temperature in specific-heat measurements. 1,3,13 The transition temperature T S depends basically on the size of the R-type ion present in the structure 6 and one observes a decreasing T S by increasing the R radius. In particular, one finds T S = 201.5 K, 155 K, and 445 K for the Tb-, Gd-, and Y-based compounds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a rich variety of interesting structural and dielectric properties has been observed in these materials, partially coupled to the systems' magnetism, which is evidenced by a plethora of structural and magnetic phase transitions which depend on the rare-earth ion. [1][2][3][4][5][6][7][8] Furthermore, magnetoelectric coupling and multiferroic features, i.e., the coexistence of elastic, magnetic, and electric order parameters have been reported for the Nd-and Gdbased compounds. [8][9][10][11] At room temperature RFe 3 ͑BO 3 ͒ 4 compounds crystallize in the space group R32.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the polarization along the a and c axes are related to the magnetic field induced ordering at the Fe and Ho sites, respectively. This behavior is not observed in the R = Y, Er [27], and Tb systems [28].…”
Section: Introductionmentioning
confidence: 83%